Building Institutional Repositories in Sudan: Keys to Success - Abdelrahman, Iman Abuel Maaly (My University, 2015)
An Institutional Repository (IR) is a set of services that a university offers to its community members for the management and dissemination of digital materials created by its researchers and staff members. IR establishment is a challenge for information professionals because the main goal for implementing IRs is to provide Open Access (OA) to institution research output. The growth of open access institutional repositories has been very remarkable in the developed countries. However, in most of the developing countries like Sudan awareness of the concept of open access and IR is very low. Since its foundation, the Sudanese Research and Education Network (SudREN) has successfully implemented several library projects. The most successful one was a project funded by UNESCO in 2013. The main objective of that project was to implement Library Management Systems (LMS) and Institutional Repositories (IR) for three Sudanese universities based on open source Software Systems. Project components were technical and operational training, software customization, and hardware preparations. The main role played by SudREN was providing administrative and financial services through the Steering Committee that acted as an advisory body for the project during its lifetime. In addition to that, SudREN provided technical support to the project team. This paper describes the capacity requirements for SudREN to support the provision and use of value-added services to its member institutions focusing on the IR project. It describes the key success factors in implementing IRs in the Sudanese universities. It also discusses the opportunities and challenges facing the project to reach its ultimate goal. This paper gives examples of successful collaboration in practice between the three key groups of professionals – librarians, IT/information systems professionals, and engineers – whose collaboration have done much to the success of the project. The paper provides lessons learned and concludes ways of overcoming obstacles and achieving productive mutual understanding among SudREN’s stakeholders and with other players.